2018
DOI: 10.1212/wnl.0000000000006155
|View full text |Cite
|
Sign up to set email alerts
|

Education Research: A framework for global health curricula for neurology trainees

Abstract: As the global burden of neurologic disease increases, educating future neurologists about the principles of global health through global health curricula is of utmost importance. However, few neurology residency training programs have developed and implemented comprehensive global health curricula. This report outlines the design, implementation, and evaluation of the University of Massachusetts Medical School neurology residency global health curriculum. Using accepted curriculum development methods and incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Interest in global health has increased among undergraduate students, medical students, and residents, [1][2][3] including neurology residents, [4] likely reflecting the growing burden of neurological disease in low-and middle-income countries. [5][6] However, formalized global neurology training tracks [7] and curricula are rare, [8] with only one-half of US and Canadian neurology programs offering global health electives, [4] thus potentially limiting resident training and exposure to the field.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in global health has increased among undergraduate students, medical students, and residents, [1][2][3] including neurology residents, [4] likely reflecting the growing burden of neurological disease in low-and middle-income countries. [5][6] However, formalized global neurology training tracks [7] and curricula are rare, [8] with only one-half of US and Canadian neurology programs offering global health electives, [4] thus potentially limiting resident training and exposure to the field.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, medical schools and residencies have sought to standardize medical education experiences to maximize training opportunities 8 . The benefits of developing global health experiences for residents have been shown to include improvements in medical knowledge, resourcefulness, cultural and interpersonal competence, and career development 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 The benefits of developing global health experiences for residents have been shown to include improvements in medical knowledge, resourcefulness, cultural and interpersonal competence, and career development. 9 Multiple specialties have successfully incorporated these experiences into residency and fellowship training. For example, a study of neurology fellowship trainees demonstrated that increasing the awareness of global health issues exposed them to the burden of disease and lack of medical experts in certain parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…They have proven to be of particular value during this COVID 19 pandemic to enforce social distancing locally and to facilitate rapid sharing of medical experience across countries. Although 30-50% of neurology programs in North America allow international clinical and research exchanges, the majority of residents lack exposure to the practice of neurology abroad [4].…”
Section: Introductionmentioning
confidence: 99%